A Hammett Study of Clostridium acetobutylicum Alcohol Dehydrogenase (CaADH): An Enzyme with Remarkable Substrate Promiscuity and Utility for Organic Synthesis - Kudalkar, Gaurav P.; Tiwari, Virendra K.; Lee, Joshua D.; Berkowitz, David B. (Synlett, 2020)
Described is a physical organic study of the reduction of three sets of carbonyl compounds by the NADPH-dependent enzyme Clostridium acetobutylicum alcohol dehydrogenase (CaADH). Previous studies in our group have shown this enzyme to display broad substrate promiscuity, yet remarkable stereochemical fidelity, in the reduction of carbonyl compounds, including α-, β- and γ-keto esters (d-stereochemistry), as well as α,α-difluorinated-β-keto phosphonate esters (l-stereochemistry). To better mechanistically characterize this promising dehydrogenase enzyme, we report here the results of a Hammett linear free-energy relationship (LFER) study across three distinct classes of carbonyl substrates; namely aryl aldehydes, aryl β-keto esters and aryl trifluoromethyl ketones. Rates are measured by monitoring the decrease in NADPH fluorescence at 460 nm with time across a range of substrate concentrations for each member of each carbonyl compound class. The resulting v0 versus [S] data are subjected to least-squares hyperbolic fitting to the Michaelis–Menton equation. Hammett plots of log(Vmax) versus σX yield the following Hammett parameters: (i) for p-substituted aldehydes, ρ = 0.99 ± 0.10, ρ = 0.40 ± 0.09; two domains observed, (ii) for p-substituted β-keto esters ρ = 1.02 ± 0.31, and (iii) for p-substituted aryl trifluoromethyl ketones ρ = –0.97 ± 0.12. The positive sign of ρ indicated for the first two compound classes suggests that the hydride transfer from the nicotinamide cofactor is at least partially rate-limiting, whereas the negative sign of ρ for the aryl trifluoromethyl ketone class suggests that dehydration of the ketone hydrate may be rate-limiting for this compound class. Consistent with this notion, examination of the 13C NMR spectra for the set of p-substituted aryl trifluoromethyl ketones in 2% aqueous DMSO reveals significant formation of the hydrate (gem-diol) for this compound family, with compounds bearing the more electron-withdrawing groups showing greater degrees of hydration. This work also presents the first examples of the CaADH-mediated reduction of aryl trifluoromethyl ketones, and chiral HPLC analysis indicates that the parent compound α,α,α-trifluoroacetophenone is enzymatically reduced in 99% ee and 95% yield, providing the (S)-stereoisomer, suggesting yet another compound class for which this enzyme displays high enantioselectivity.
Keywords: linear free-energy relationships; Hammett study; Clostridium acetobutylicum ADH; stereochemical fidelity; enzyme promiscuity; trifluoromethyl ketones